2007
DOI: 10.1017/s000711450773461x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial substitution of dietary fish oil with blends of vegetable oils, on blood leucocyte fatty acid compositions, immune function and histology in European sea bass (Dicentrarchus labrax L.)

Abstract: Within a decade or so insufficient fish oil (FO) will be available to meet the requirements for aquaculture growth. Consequently, alternative sources are being investigated to reduce reliance on wild fish as a source of FO. Vegetable oils (VO) are a feasible alternative to FO. However, it is important to establish that alternative dietary lipids are not only supplied in the correct quantities and balance for optimal growth, but can maintain immune function and prevent infection, since it is known that the nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 39 publications
10
71
0
1
Order By: Relevance
“…In addition to absolute ARA levels, the balance between ARA and EPA (precursor to the lesspotent eicosanoids, 3-series prostanoids and 5-series leukotrienes) in the tissues appears to influence physiological status in aquatic species. Given the relationship between dietary FA composition and tissue profile, it is not surprising that replacing fish oil with various plant-derived lipids influences eicosanoid production [58] and, in turn, processes regulated by eicosanoids such as immune function [56,[59][60][61] . However, most of these studies, in spite of having compared feeds with radically different fatty acid profiles, have reported moderate or conflicting immunological effects.…”
Section: Comparative Physiological Effectsmentioning
confidence: 99%
“…In addition to absolute ARA levels, the balance between ARA and EPA (precursor to the lesspotent eicosanoids, 3-series prostanoids and 5-series leukotrienes) in the tissues appears to influence physiological status in aquatic species. Given the relationship between dietary FA composition and tissue profile, it is not surprising that replacing fish oil with various plant-derived lipids influences eicosanoid production [58] and, in turn, processes regulated by eicosanoids such as immune function [56,[59][60][61] . However, most of these studies, in spite of having compared feeds with radically different fatty acid profiles, have reported moderate or conflicting immunological effects.…”
Section: Comparative Physiological Effectsmentioning
confidence: 99%
“…As stated in a previous study, the use of n-6 and n-3 (PUFA) and MUFA fatty acids as an alternative and source of energy led to significant effects in the immune system and supported macrophage activity of fish (Barros et al, 2002;Montero et al, 2005;Mourente et al, 2007;Montero and Izquerdo, 2010). Mourente et al (2007) stated that the use of vegetable derived lipids as an alternative to fish oil yielded optimal growth and feed cycle and can also optimize immune system functions of fishes if it is included in the right amounts.…”
Section: Introductionmentioning
confidence: 83%
“…There have been numerous studies into the effects of balanced diet contents on hematological parameters (Robinson and Daniels, 1987;Mourente et al, 2007;Wassef et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have reported considerable success in partial or total replacement of FO with VO in many fish species (Ng, 2005;Turchini et al, 2009Turchini et al, , 2010. Moreover, recent studies have also evaluated the effects of replacing highquality FO with VO sources on growth performance, fatty acid profile or health parameters of fishes, such as gilthead seabream (Sparus aurata) (Menoyo et al, 2004) and European sea bass (Dicentrarchus labrax L.) (Mourente et al, 2007). However, the extent of the effect is determined by the vegetable oil source and level of dietary replacement.…”
Section: Introductionmentioning
confidence: 99%